International Trade with Firm Heterogeneity in Factor Shares - Julian Emami Namini (Tinbergen Institute, 2009)
This paper presents a trade model with capital and labor as factors of production. The main contribution of this paper is that it considers a new type of firm heterogeneity, which is empirically relevant: firms in this paper differ with respect to their factor shares in production. Therefore, this paper addresses the following four empirical facts on globalization, firms' factor shares and factor prices: (i) firms within narrowly defined industries exhibit a large degree of heterogeneity in factor shares in production; (ii) exporters are, on average, more capital intensive than non—exporters; (iii) globalization decreases labor's share in national income; (iv) the larger the share of exporters in the industry, the larger the increase in the industry's wages due to globalization.
Keywords: F12; L11; 330; two—factor trade model; firm heterogeneity in factor shares; Intraindustrieller Handel; Produktionsfaktor; Faktorpreis; Allgemeines Gleichgewicht; Mehr-Sektoren-Modell; Optimales Wachstum; Außenwirtschaftstheorie; Theorie